THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON ENTREPRENEURSHIP BEHAVIOR IN IMPROVING CLOVE FARMING PERFORMANCE IN CENTRAL MALUKU DISTRICT, MALUKU PROVINCE - Gloria Matital; Wiludjeng Roessali; Vitus Dwi Yunianto (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The clove is one of many commodities that have economic value and contributes to improving government revenues. This research aimed to determine the influence of internal factors and external factors on entrepreneurship behavior in improving farming performance. Studies were conducted on 100 sampling farmers, with data collection techniques of interviews and using questionnaires. The data was analyzed using Structural Equation Model (SEM) with Lisrel software. The results showed that internal factors (X1) which consisted of age, education level, length of business, motivation, business scale simultaneously had a positive effect on entrepreneurship behavior. External factors (X2) consisting of the availability of inputs and institutions simultaneously have a positive influence on entrepreneurship behavior.